Case report: Twice-daily tolvaptan dosing regimen in a challenging case of hyponatremia due to SIAD - Arecco, Anna; Demontis, Davide; Della Sala, Leonardo; Musso, Natale; Gay, Stefano; Boschetti, Mara; Ferone, Diego; Gatto, Federico (Frontiers in Endocrinology, 2024)
Background Syndrome of inappropriate antidiuresis (SIAD) is one of the most frequent causes of euvolemic hyponatremia (serum sodium levels < 135 mEq/L) and it represents more than 35% of hyponatremia cases in hospitalised patients. It is characterised by an inappropriate vasopressin (AVP)/antidiuretic hormone (ADH) secretion, which occurs independently from effective serum osmolality or circulating volume, leading to water retention via its action on type 2 vasopressin receptor in the distal renal tubules. Corpus callosum agenesis (CCA) is one of the most common congenital brain defects, which can be associated to alterations in serum sodium levels. This report presents a rare case of chronic hyponatremia associated with SIAD in a woman with CCA, whose correction of serum sodium levels only occurred following twice-daily tolvaptan administration.Case presentation A 30-year-old female was admitted to our hospital for non-acute hyponatremia with dizziness, headache, distal tremors, and concentration deficits. She had profound hyponatraemia (Na 121 mmol/L) with measured plasma hypo-osmolality (259 mOsm/Kg) and urinary osmolality greater than 100 mOsm/Kg (517 mOsm/Kg). She presented clinically as normovolaemic. After the This is a provisional file, not the final typeset article exclusion of other causes of normovolemic hyponatraemia, such as hypothyroidism and adrenal insufficiency, a diagnosis of SIAD was established. We have ruled out paraneoplastic, inflammatory, and infectious causes, as well as ischemic events. Her medical history showed a CCA and frontal teratoma. We administered tolvaptan initially at a low dosage (15 mg once a day) with persistence of hyponatraemia. Therefore, the dosage was first doubled (30 mg once a day) and then increased to 45 mg once a day with an initial improvement in serum sodium levels, although not long-lasting. We therefore tried dividing the 45 mg tolvaptan administration into two doses of 30 mg and 15 mg respectively, using an off-label treatment schedule, thus achieving long-lasting serum sodium levels in the low-normal range associated with a general clinical improvement.This report underlines the importance of the correct diagnosis, management and treatment of SIAD, as well as the need for further studies about the pharmacokinetics and pharmacodynamics of vasopressin receptor antagonists.